2015
DOI: 10.7196/samjnew.8172
|View full text |Cite
|
Sign up to set email alerts
|

Codeine misuse and dependence in South Africa – learning from substance abuse treatment admissions

Abstract: Data from treatment admissions related to codeine misuse and dependence are informative, but provide an incomplete picture of the nature and extent of codeine-related problems in SA. Other data sources must be considered before further regulatory/policy changes regarding codeine are implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 9 publications
4
31
0
Order By: Relevance
“…[6] Research in SA has indicated that there were 435 admissions to specialist substance abuse treatment centres for codeine misuse or dependence in 2014, translating to ~2.5% of individuals seen in such settings. [7] This is fairly similar to figures from the UK (2.2%) and Ireland (1.9%). [6] However, these figures do not include individuals treated at public or private psychiatric treatment facilities.…”
Section: Researchsupporting
confidence: 78%
“…[6] Research in SA has indicated that there were 435 admissions to specialist substance abuse treatment centres for codeine misuse or dependence in 2014, translating to ~2.5% of individuals seen in such settings. [7] This is fairly similar to figures from the UK (2.2%) and Ireland (1.9%). [6] However, these figures do not include individuals treated at public or private psychiatric treatment facilities.…”
Section: Researchsupporting
confidence: 78%
“…Codeine dependence and associated morbidity relating to codeine misuse have been reported globally . Tolerance to, and dependence on, codeine are particularly problematic if dose escalation occurs and the patient is using combination products, as this will result in excessive exposure to both analgesics, leading to serious morbidities and occasionally death, as documented in recent studies and case reports . While the prevalence of codeine dependence in regions where codeine is available OTC is largely unknown, an Australian survey found 17% of 800 recent users of combination analgesics containing codeine (CACC) screened positive for codeine dependence (using Severity of Dependence Scale), with those identified as dependent taking either maximum or excessive daily doses of these products, often for many years .…”
Section: Introductionmentioning
confidence: 99%
“…SA is considering introducing regulations to reduce the amount of codeine in a tablet to 10 mg and to up-schedule norcodeine and acetylcodeine. Dada et al [5] analysed substance abuse treatment admissions to investigate the extent of treatment demand related to the misuse of codeine or codeine dependence in SA and the profile of patients seeking treatment for their misuse or dependency on codeine (as part of a comprehensive, multicountry Codeine Misuse and Dependence (Codemisused) Study funded by the European Union). Fewer than 1% of persons had codeine as their primary substance of abuse, similar to findings reported from centres in the UK and Ireland.…”
Section: Codeine Misuse and Dependence In Samentioning
confidence: 99%